2023
DOI: 10.1186/s12864-023-09604-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and bioinformatics analysis of the WD40 transcription factor family and candidate gene screening for anthocyanin biosynthesis in Rhododendron simsii

Cheng Wang,
Yafang Tang,
Yan Li
et al.

Abstract: WD40 transcription factors (TFs) constitute a large gene family in eukaryotes, playing diverse roles in cellular processes. However, their functions in the major ornamental plant, Rhododendron simsii, remain poorly understood. In this study, we identified 258 WD40 proteins in the R. simsii genome, which exhibited an uneven distribution across chromosomes. Based on domain compositions and phylogenetic analysis, we classified these 258 RsWD40 proteins into 42 subfamilies and 47 clusters. Comparative genomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Thes The HD-ZIP transcription factors can improve the morphological characteristics of plants under abiotic stress. Sorghum is characterized by its small genome and short life cycle [67]. A relevant study indicated that, among the 1644 common differentially expressed genes (DEGs) in sorghum roots under severe drought stress and rehydration treatments, 2 HD-ZIP genes were upregulated under drought stress and downregulated under rehydration treatments while 4 HD-ZIP genes were downregulated under drought stress and upregulated under rehydration treatments.…”
Section: Response Of Hd-zip Transcription Factors To Drought Stressmentioning
confidence: 99%
“…Thes The HD-ZIP transcription factors can improve the morphological characteristics of plants under abiotic stress. Sorghum is characterized by its small genome and short life cycle [67]. A relevant study indicated that, among the 1644 common differentially expressed genes (DEGs) in sorghum roots under severe drought stress and rehydration treatments, 2 HD-ZIP genes were upregulated under drought stress and downregulated under rehydration treatments while 4 HD-ZIP genes were downregulated under drought stress and upregulated under rehydration treatments.…”
Section: Response Of Hd-zip Transcription Factors To Drought Stressmentioning
confidence: 99%